MATHEMATICAL MODEL OF PIN DEFERRIZATION OF WATER (Municipal economy of cities. Series: «Economy science», 2016)
There is a far of methods of deferrization of water to date, constructions of filters and filings up for them, however there is an universal, economic advantageous method of deferrization of water. In every case for the deferrization of water it is necessary to use concrete methods and waste-water treatment facility. The mathematical model of deferrization of water is based on two basic blocks: lighting (deformation) block which takes into account financial balance and kinetics of flowing of process and hydrodynamic (lauter), which describes the dynamics of losses of pressure in a grainy load. At the deferrization of water with separate vozdukhootdelitelyami and indirect cost, speed of filtration on each of filters will be permanent. At general vozdukhootdelitele for a few penopolistirol’nykh filters, they will work with different speed. Speed of filtration changes at the change of rate-of-flow, given on a deferrization, that characteristically at a multiarea tariff on electric power. In periods of minimum electricity charges filters work with the maximally possible productivity, and in periods of maximal cost – work with a minimally necessary expense or does not work in general. Researches rotined that porosity of load insignificantly increased at the increase of granules. It is set that an important index at the design of contact deferrization of water is dependence of initial concentration of sediment after washing on a height sloya loads. With the sufficient degree of exactness mathematical balance can be presented equalization, which takes into account speed of filtration, washing of filter and rational expense of electric power. The mathematical model of contact deferrization of water is developed on grainy filters. The basic blocks of deferrization of water are resulted the designs of contact deferrization of water fixed in basis. The algorithm of realization of mathematical model is presented, which can be realized in any programming language or in the specialized software products and which plugs in itself the followings principal items: necessary coefficients and steps of account are set on the height of load and time, the arrays of middle diameters, initial distributing of sediment, are determined on the height of load, coefficients of tearing away and adhesion of particles, the two embedded loops get organized – at times filtrations and on the height of load, efficiency of deferrization of water is determined on the layers of load, closeness of sediment, porosity, hydraulic slope and losses of pressure at the fixed value of time of filtration, time of filtration and calculations of parameters is increased on a height sloya, if necessary, verification of implementation of certain terms (for example, quality of filtrate, losses of pressure) can be organized, with subsequent clarification of basic data (for example, adjustments of general height of load, speeds of filtration). The results of researches can be presented as tables and charts. Verification of model adequacy well comports with experimental researches, that allows to recommend the developed model for practical calculations. Keywords: deferrizations of water, hydraulic slope, polystyrene filters, grain-size distribution of loading,parameters of work of grainy filters, concentration of iron, waste-water treatment facility.